FEMALE CONSCIOUS BEHAVIOR REGARDING THE USE OF LANGUAGE DURING CONVERSATION: AN ANALYTICAL STUDY OF FEMALE TALK ON MEDIA - Saifullah Zafar; Maria Imtiaz; Rashda Perveen (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
The present study explores the female conscious behavior regarding the use of language during conversation: an analytical study of female talks on media. In order to see the difference in language of both genders, the data were collected from 5 television talk shows. The data were examined based on the linguistics behavior; hedges, hypercorrect grammar, intensifiers, modal verbs, and special connecting words in Urdu. To examine the data, both qualitative and quantitative methodologies were used. SPSS was used to determine the importance in the language of both genders. There were considerable differences in the language usages of both sexes. Females were shown to be more aware of their language use. Only the casual portions of communication were included in this study. Additionally, newspapers, periodicals, etc. might serve as data sources for future investigations.